The Low-Density Cities: Problems and Management. - Fregolent, Laura (TeMA - Journal of Land Use, Mobility and Environment, 2012)
The essay explores the phenomenon of low-density city. It is divided into three main parts in which are described the characters, the changes and the forms of the phenomenon in different contexts. In the first part are highlighted character and evolution of the phenomenon in several European and North American contexts, while the second describes the transformation and evolution of a specific context: the territorial system of the central Veneto region. It is a particular example of sprawl occurred in the last forty years that a profound changes in physical, morphological and socio-economic characteristics of the area. In the third part of the essay some examples of policy and planning tools for containing the land consumption and resources in a sustainable way.